Assessing the use of dual-drainage modeling to determine the effects of green stormwater infrastructure networks on events of roadway flooding - Knight, Kathryn, author; Bhaskar, Aditi, advisor; Arabi, Mazdak, committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2020)
Roadway flooding occurs when a stormwater network does not have the capacity to drain all runoff generated by precipitation. Roadway flooding causes damage to infrastructure and property, risks to human health and safety, and disruptions to transportation systems. Green stormwater infrastructure (GSI) has been increasingly used to reduce stormwater input to the subsurface stormwater network, stormwater draining to urban streams, and to improve water quality. It is unclear how GSI interacts with surface runoff and stormwater structures to affect the spatial extent and distribution of roadway flooding. This interaction was explored using a dual drainage model with individual stormwater structures represented, fine spatial resolution, and bidirectional flow between the subsurface stormwater network and surface runoff. The model was developed using the Stormwater Management Model for PC (PCSWMM) in the urban watershed Harvard Gulch in Denver, Colorado. We examined how dual drainage modeling could reveal the effect of converting between 1% and 5% of directly connected impervious area (DCIA) in the watershed to bioretention GSI on the extent, depth, and distribution of roadway flooding. Results of the surface flooding model were generally co-located with resident reports related to flooding within the study area. Results show that even for 1% of DCIA converted to GSI, the extent and mean depth of roadway flooding was reduced for the duration of the simulation, and increasing GSI conversion further reduced roadway flooding depth and extent. We found diminishing returns in the roadway flood extent reduction per additional percentage of DCIA converted to GSI beyond 2.5%, whereas diminishing returns occurred beyond 1% conversion to GSI for mean roadway flood depth reduction. This work also examined the limitations to the accurate representation of roadway flooding due to incomplete input data, a lack of observational data for urban floods, GSI placement methods, and high computational demands. With future work to reduce limitations, detailed dual drainage modeling has the potential to better predict what strategies will mitigate roadway flooding.
Keywords: green stormwater infrastructure; stormwater; dual drainage modeling; urban flooding; roadway flooding